2012
DOI: 10.1002/stem.1060
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Maturation Culture Favors a Reduction in the Tumorigenicity and the Dopaminergic Function of Human ESC‐Derived Neural Cells in a Primate Model of Parkinson's Disease

Abstract: For the safe clinical application of embryonic stem cells (ESCs) for neurological diseases, it is critical to evaluate the tumorigenicity and function of human ESC (hESC)-derived neural cells in primates. We have herein, for the first time, compared the growth and function of hESCderived cells with different stages of neural differentiation implanted in the brains of primate models of Parkinson's disease. We herein show that residual undifferentiated cells expressing ESC markers present in the cell preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 47 publications
2
114
1
Order By: Relevance
“…All animals received a daily dose of ampicillin (100 mg/kg) for 1 week after cell engraftment and a subcutaneous injection of tacrolimus (0.05 mg/kg; Astellas Pharma, Inc., Tokyo, Japan, http://www. astellas.com) [28] until they were sacrificed. At 10 weeks after transplantation, magnetic resonance imaging (MRI) was performed with the marmosets under general anesthesia, as described previously [18].…”
Section: Contusive Sci and Transplantation In Common Marmosetsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animals received a daily dose of ampicillin (100 mg/kg) for 1 week after cell engraftment and a subcutaneous injection of tacrolimus (0.05 mg/kg; Astellas Pharma, Inc., Tokyo, Japan, http://www. astellas.com) [28] until they were sacrificed. At 10 weeks after transplantation, magnetic resonance imaging (MRI) was performed with the marmosets under general anesthesia, as described previously [18].…”
Section: Contusive Sci and Transplantation In Common Marmosetsmentioning
confidence: 99%
“…Motor function was evaluated using the original open field rating scale score for general motor function and the bar grip test for grip strength [28]. The score in the original open field rating scale decreased to near zero shortly after contusive SCI.…”
Section: Esc-ns/pc Transplantation Promoted Functional Recovery Aftermentioning
confidence: 99%
“…The accumulation of excess iron promotes oxidative damage to tissues, which can ultimately lead to failure of organs such as the heart, liver, and endocrine glands. Hepcidin levels are inappropriately low relative to body iron stores in another class of clinical disorders associated with systemic iron loading: congenital anemias that are characterized by ineffective erythropoiesis (IE) (2). IE describes a defective form of erythroid maturation characterized by an increased proportion of erythroid precursors, which, due to excessive apoptosis, fail to produce the normal complement of mature erythrocytes.…”
Section: Conflict Of Interest: the Authors Have Declared That Nomentioning
confidence: 99%
“…SDIA-induced neurons contain high amounts of DA neurons and are integrated into the 6-OHDA-lesioned mouse striatum after transplantation. Additionally, it has been proven that functional DA neurons can be differentiated from primate and human ESCs using SDIA [45,46]. Therefore, the establishment of the SDIA method opened new fields for both basic neuroscience research and therapeutic applications.…”
Section: Induction Of Midbrain Da Neurons In Vitro From Escs/ipscsmentioning
confidence: 99%
“…In addition, motor symptoms are also improved by grafting human ESCderived DA neurons that have maturated over a long term (42 days). These results suggest that human ESC-derived DA neurons that are differentiated for appropriate terms strongly contribute to both reducing the risk of tumor genesis and improving parkinsonian motor dysfunction [46]. Recently, we first reported that human iPSC-derived DA neurons that are differentiated under feeder-free and serum-free conditions survived in an MPTP-lesioned primate parkinsonian model for six months [63].…”
Section: Preclinical Trials Of Human Escs/ipsc-derived Da Neurons For Pdmentioning
confidence: 99%